Like it or not? How the Economic and Institutional Environment Shapes Individual Attitudes towards Multinational Enterprises - Philipp Harms; Jakob Schwab (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper analyzes the determinants of people s attitudes towards FDI using a survey-based data set that covers a wide range of rich and poor countries. We find that both individual socioeconomic characteristics and macroeconomic factors shape agents attitudes towards multinational firms. Moreover, we find that the influence of an individual s characteristics such as employment status and education depends on the respective country s per-capita income.
Keywords: F21; F23; F61; 330